The Applications of the Rule of ‘Al-Wahid’ in Islamic Sciences - Seyyed Mohsen Miri (حکمت اسرا, 2010)
Muslim scholars have applied the Rule of ‘Al-WÁhid’ to various sciences and subjects. The article expounds and analyses some of the usages of the Rule in such sciences as metaphysics, natural philosophy, and the principles of jurisprudence.